The validity and contributing physiological factors to 30-15 intermittent fitness test performance in rugby league - Scott, T. J.; Duthie, G. M.; Delaney, J. A.; Sanctuary, C. E.; Ballard, D. A.; Hickmans, J. A.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2017)
This study examined the validity of the 30-15 Intermittent Fitness Test (30-15IFT) within rugby league. Sixty-three Australian elite and junior-elite rugby league players (22.5 ± 4.5 years, 96.1 ± 9.5 kg, S7 skinfolds: 71.0 ± 18.7 mm) from a professional club participated in this study. Players were assessed for anthropometry (body mass, S7 skinfolds, lean mass index), prolonged high-intensity intermittent running (PHIR; measured by 30-15IFT), predicted aerobic capacity (MSFT) and power (AAS), speed (40 m sprint), repeated sprint, and change of direction (COD—505 agility test) ability before and after an 11-week preseason training period. Validity of the 30-15IFT was established using Pearson's coefficient correlations. Forward stepwise regression model identified the fewest variables that could predict individual final velocity (V IFT) and change within 30-15IFT performance. Significant correlations between V IFT and S7 skinfolds, repeated sprint decrement, VO2maxMSFT, and average aerobic speed were observed. A total of 71.8% of the adjusted variance in 30-15IFT performance was explained using a 4-step best fit model (VO2maxMSFT, 61.4%; average aerobic speed, 4.7%; maximal velocity, 4.1%; lean mass index, 1.6%). Across the training period, 25% of the variance was accounted by dVO2maxMSFT (R 2 = 0.25). These relationships suggest that the 30-15IFT is a valid test of PHIR within rugby league. Poor correlations were observed with measures of acceleration, speed, and COD. These findings demonstrate that although the 30-15IFT is a valid measure of PHIR, it also simultaneously examines various physiological capacities that differ between sporting cohorts.